Warfare, ritual, and symbol in biblical and modern contexts - Kelle, Brad E., 1973-; Ames, Frank Ritchel; Wright, Jacob L. (Atlanta : Society of Biblical Literature, 2014)
"Warfare, Ritual, and Symbol in Biblical and Modern Contexts is a collection of fifteen essays about rituals of war and their function. Comparative and interdisciplinary approaches are applied to texts in the Hebrew Bible, which are read in light of ancient Near Eastern literature, artifacts, and iconography and contemporary ritual and social theory. Introductory and concluding essays evaluate each contribution, locate contributions in the history of scholarship, and propose promising directions for further research. A majority of the essays were presented in 2010-12 sessions of the SBL's Warfare in Ancient Israel Section"--
Includes bibliographical references and index.
Description based on print version record.
Keywords: War -- Biblical teaching; Bible. -- Criticism, interpretation, etc; Middle Eastern literature -- History and criticism; RELIGION / Biblical Studies / Old Testament; RELIGION / Judaism / Sacred Writings; Electronic books